2014
DOI: 10.1007/s00408-014-9558-9
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Exercise Training in Patients with Pulmonary Hypertension

Abstract: This is the first study to investigate the cost-effectiveness of exercise training in PH. Due to less worsening events within 2 years, healthcare costs were lower in patients performing exercise training as add-on to medical therapy than in patients with medical treatment only. Further prospective, randomized studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
2
26
1
3
Order By: Relevance
“…A recent report also demonstrated that exercise training may lead to reduced health care costs (reduction in costs of EUR 657/patient within a period of 2 years) [33]. The main cost reduction was caused by less initiation of PH-targeted treatment.…”
Section: Clinical Effects Of Exercise Training On Phmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report also demonstrated that exercise training may lead to reduced health care costs (reduction in costs of EUR 657/patient within a period of 2 years) [33]. The main cost reduction was caused by less initiation of PH-targeted treatment.…”
Section: Clinical Effects Of Exercise Training On Phmentioning
confidence: 99%
“…However, even though some studies reported excellent survival rates over a follow-up period of up to 3 years (97-100% at 1 year, 94-100% at 2 years and 80-86% at 3 years) [10,11,33,34], to date no study was designed to assess whether exercise training provided patients with a measurable survival advantage. An RCT with survival or at least time to clinical worsening as primary endpoint would be necessary and useful.…”
Section: Clinical Effects Of Exercise Training On Phmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 and 15 weeks, patients significantly improved the 6MWD compared to baseline, scores of quality of life, WHO functional class, peak oxygen consumption, oxygen pulse, HR and systolic pulmonary artery pressure at rest and maximal workload (71). Due to less worsening events within 2 years, average healthcare costs lower of €675,00 in the group of patients who performed a specialized rehabilitation program (72). Obviously, non-RCT design presented several potential bias, but no published study contrasted the safety and potential benefits of ET for PAH patients anyway.…”
Section: Other Non-rcts Studies In Humansmentioning
confidence: 95%
“…4 Notwithstanding these pitfalls, the role of exercise training does appear to have significant benefits as an adjunct to pharmacotherapy and has been shown to be cost-effective in a European setting. 5 However, the expansion of these findings to a global context is crucial for the inclusion of exercise training in the PH treatment and rehabilitation guidelines. There is therefore a great need for more robust clinical trials in this area of exercise training for patients with PH.…”
mentioning
confidence: 99%